2023
DOI: 10.1021/acs.jafc.2c05996
|View full text |Cite
|
Sign up to set email alerts
|

Pectate Lyase Gene VvPL1 Plays a Role in Fruit Cracking of Table Grapes

Abstract: Fruit cracking seriously affects the commercial value of table grapes. To explore whether cell wall disassembly influences grape berry cracking, first, the differences in the cell wall metabolism were compared between cracking-resistant "Shennongjinhuanghou" (SN) and cracking-susceptible "Xiangfei" (XF) varieties. Our results showed that cell wall disassembly events were extremely different between "SN" and "XF." The cracking-resistant "SN" had a higher pectinmethylesterase activity in the early stage and lowe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 78 publications
0
4
0
Order By: Relevance
“…Previous studies have shown that increased activity of these enzymes and proteins leads to fruit softening [63]. The low activity of pectinase synergistically inhibited the degradation of cell walls and increased their resistance to cleavage after the color change stage in grapes [64]. The genes encoding these enzymes and proteins may also have synergistic effects with each other [35].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that increased activity of these enzymes and proteins leads to fruit softening [63]. The low activity of pectinase synergistically inhibited the degradation of cell walls and increased their resistance to cleavage after the color change stage in grapes [64]. The genes encoding these enzymes and proteins may also have synergistic effects with each other [35].…”
Section: Discussionmentioning
confidence: 99%
“…A dramatic result of the altered skin structure was greatly increased water permeance and subsequent post‐harvest fruit water loss. Increased skin cracking can be a consequence of altered cell wall structure, as shown in tomato where the cell wall structure was affected by silencing of the β‐galactosidase gene TBG6 , silencing of SlEXP1/SlPG2a , or by overexpression of the grape PL VvPL1 (Jiang et al., 2019; Moctezuma et al., 2003; Yu et al., 2023). The higher permeance of apple fruit in the PGox lines was also related to microcracking of the cuticle.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous factors have been identified in research as closely associated with fruit-cracking, including temperature, moisture, light, hormones, mineral elements, skin mechanical properties, and skin strength. , However, the specific causes of fruit-cracking can vary among the different species. The excessive enlargement of fruit flesh cells, exceeding the tolerance of the fruit skin, is often considered as a significant factor leading to fruit-cracking. One important reason for cell enlargement is the regulation of osmotic pressure by cell inclusions . Soluble sugars are crucial cellular components that not only contribute to fruit growth and development, but also provide the osmotic driving force for fruit cell expansion .…”
Section: Introductionmentioning
confidence: 99%
“…6−10 One important reason for cell enlargement is the regulation of osmotic pressure by cell inclusions. 11 Soluble sugars are crucial cellular components that not only contribute to fruit growth and development, but also provide the osmotic driving force for fruit cell expansion. 12 Lu and Lin (2012) discovered that cracked apples had 20% higher levels of soluble solids and titratable acid content compared to normal fruits, along with a 40% lower osmotic potential and a 60% higher swelling pressure.…”
Section: Introductionmentioning
confidence: 99%